Elevated Expression of Serotonin 5-HT2A Receptors in the Rat Ventral Tegmental Area Enhances Vulnerability to the Behavioral Effects of Cocaine - Herin, David V.; Bubar, Marcy J.; Seitz, Patricia K.; Thomas, Mary L.; Hillman, Gilbert R.; Tarasenko, Yevgeniya I.; Wu, Ping; Cunningham, Kathryn A. (Frontiers in Psychiatry, 2013)
The dopamine mesocorticoaccumbens pathway which originates in the ventral tegmental area (VTA) and projects to the nucleus accumbens and prefrontal cortex is a circuit important in mediating the actions of psychostimulants. The function of this circuit is modulated by the actions of serotonin (5-HT) at 5-HT2A receptors (5-HT2AR) localized to the VTA. In the present study, we tested the hypothesis that virally mediated overexpression of 5-HT2AR in the VTA would increase cocaine-evoked locomotor activity in the absence of alterations in basal locomotor activity. A plasmid containing the gene for the 5-HT2AR linked to a synthetic marker peptide (Flag) was created and the construct was packaged in an adeno-associated virus vector (rAAV-5-HT2AR-Flag). This viral vector (2 μl; 109–10 transducing units/ml) was unilaterally infused into the VTA of male rats, while control animals received an intra-VTA infusion of Ringer’s solution. Virus-pretreated rats exhibited normal spontaneous locomotor activity measured in a modified open-field apparatus at 7, 14, and 21 days following infusion. After an injection of cocaine (15 mg/kg, ip), both horizontal hyperactivity and rearing were significantly enhanced in virus-treated rats (p < 0.05). Immunohistochemical analysis confirmed expression of Flag and overexpression of the 5-HT2AR protein. These data indicate that the vulnerability of adult male rats to hyperactivity induced by cocaine is enhanced following increased levels of expression of the 5-HT2AR in the VTA and suggest that the 5-HT2AR receptor in the VTA plays a role in regulation of responsiveness to cocaine.